DITERMINASI SOSIAL DAN LINGKUNGAN BUDAYA TERHADAP KETERAMPILAN KOGNITIF ANAK USIA DINI - Ledang, Irwan; Asshagab, Siti Mutiaraningsih (Alpatih Harapan Semesta, 2024)
This article discusses the influence of social interaction and the cultural environment on the development of cognitive skills in early childhood. Literature research was conducted to explore the influence of social interactions with parents, peers, and a rich cultural environment on children's cognitive abilities. Research shows that positive social interactions and a supportive cultural environment can optimize children's cognitive development in terms of problem solving, logical thinking, and language development. This article also offers practical implications for early childhood education.